Production of Analog Rice from Mocaf and Soybean-Based Flours for Food Diversification: A Review - Aam Sahal Mushoffi; Heny Kusumayanti; Yessy Nathania; Haliza Ramadiani (Journal of Vocational Studies on Applied Research, 2025)
This systematic review examines the production of analog rice made from Modified Cassava Flour (Mocaf) and soybean flour as part of national food diversification efforts. Through a systematic literature search conducted across Google Scholar, ScienceDirect, and the SINTA database (2013–2025), this review identifies key findings on formulation strategies, extrusion processing, and nutritional characteristics. Previous studies indicate that mocaf–soy analog rice exhibits higher protein content (8–12%), improved fiber levels, and a lower glycemic index compared to white rice. The synergy between mocaf as a carbohydrate matrix and soybean flour as a protein fortifier produces analog rice with enhanced functional and nutritional value. These findings highlight the potential of mocaf–soy analog rice as a sustainable staple alternative supporting food diversification and national food security.